2012
DOI: 10.1016/j.ydbio.2011.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog signaling is required for differentiation of endocardial progenitors in zebrafish

Abstract: Endocardial cells form the inner endothelial layer of the heart tube, surrounded by the myocardium. Signaling pathways that regulate endocardial cell specification and differentiation are largely unknown and the origin of endocardial progenitors is still being debated. To study pathways that regulate endocardial differentiation in a zebrafish model system, we isolated zebrafish NFATc1 homolog which is expressed in endocardial but not vascular endothelial cells. We further demonstrate that Hedgehog (Hh) but not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 75 publications
5
38
1
Order By: Relevance
“…To test further whether the migration of ALPM cells relies on endoderm convergence, we injected a MO targeting sox32, a transcription factor required for endoderm development (Wong et al, 2012;Yelon et al, 1999). In such morphants, which lack endoderm, the Kaede-expressing myocardial precursors failed to migrate towards the midline, remaining in the same position from 12-18 s (supplementary material Fig.…”
Section: Endoderm Convergence Controls the Initial Migration And Subdmentioning
confidence: 99%
See 1 more Smart Citation
“…To test further whether the migration of ALPM cells relies on endoderm convergence, we injected a MO targeting sox32, a transcription factor required for endoderm development (Wong et al, 2012;Yelon et al, 1999). In such morphants, which lack endoderm, the Kaede-expressing myocardial precursors failed to migrate towards the midline, remaining in the same position from 12-18 s (supplementary material Fig.…”
Section: Endoderm Convergence Controls the Initial Migration And Subdmentioning
confidence: 99%
“…The previously validated MOs targeting the following genes were injected into embryos at 1-cell stage: gna13a and gna13b (2-3 ng each) (Lin et al, 2005), s1pr2/mil (15 ng) (Kawahara et al, 2009) and sox32 (4 ng) (Wong et al, 2012).…”
Section: Morpholino (Mo) Injectionmentioning
confidence: 99%
“…Markers associated with endocardial differentiation, such as nfatc1, notch1b and klf2a, are expressed throughout the endocardium at 24-48 hpf stages in wild-type embryos and are subsequently enriched in the atrioventricular canal (AVC) (Westin and Lardelli, 1997;Oates et al, 2001;Walsh and Stainier, 2001;Wong et al, 2012). Endocardial expression of these markers was severely reduced or completely absent in hand2 −/− embryos at the analyzed stages of 22 hpf, 30 hpf (nfatc1) and 53 hpf (nfatc1, notch1b and klf2a) (Fig.…”
Section: Hand2 Is Required Within the Myocardium For Endocardial Diffmentioning
confidence: 99%
“…We have previously demonstrated that hedgehog (Hh) signaling is required for endocardial differentiation in zebrafish embryos (Wong et al, 2012). In the absence of Hh signaling, endocardial progenitors fail to migrate to the midline and do not initiate endocardial nfatc1 expression, while endothelial differentiation of blood vessels is not affected.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation